1995
DOI: 10.1038/bjc.1995.523
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 production and metabolism in human breast cancer cells and breast fibroblasts. Regulation by inflammatory mediators

Abstract: Summary Malignant human breast tumours contain high levels of prostaglandin E2 (PGE2). However, the mechanisms controlling PGE2 production in breast cancer are unknown. This in vitro study investigates the capacity for PGE2 synthesis and metabolism in several human breast cancer cell lines and early passage human breast fibroblasts and seeks to identify potential regulatory factors which may control these pathways. Basal PGE2 production rose up to 30-fold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 42 publications
1
69
0
Order By: Relevance
“…Indeed, stimulation of c-fos and Egr-1 expression by arachidonic acid in 3T3 fibroblasts has been found to depend upon PGE2 formation (Danesch et al, 1994). However, at present, we do not know the exact nature of the supporting role of PGE2 in the homeostasis of prostate cancer cells, such as that recently described for breast cancer cells (Schrey and Patel, 1995). These investigators have found that breast fibroblasts, particularly under the influence of inflammatory mediators, such as interleukin l1 and bradykinin, provide a potentially rich source for PGE2 production in breast cancer cells, whereas significant contributions from the epithelial tumour component may be restricted to breast cancer cells exhibiting an invasive phenotype (Schrey and Patel, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, stimulation of c-fos and Egr-1 expression by arachidonic acid in 3T3 fibroblasts has been found to depend upon PGE2 formation (Danesch et al, 1994). However, at present, we do not know the exact nature of the supporting role of PGE2 in the homeostasis of prostate cancer cells, such as that recently described for breast cancer cells (Schrey and Patel, 1995). These investigators have found that breast fibroblasts, particularly under the influence of inflammatory mediators, such as interleukin l1 and bradykinin, provide a potentially rich source for PGE2 production in breast cancer cells, whereas significant contributions from the epithelial tumour component may be restricted to breast cancer cells exhibiting an invasive phenotype (Schrey and Patel, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…Because established cancer cell lines are poor indicators of the tumor biology, the pathophysiological relevance of this finding is unclear at present. However, previous studies have documented that COX-2 is overexpressed in some breast cancer tissues and that enhanced prostanoid synthesis is associated with mammary tumors (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enhanced synthesis of PGE 2 , a major product of COX-2, was observed in human breast cancer as well as in experimental murine mammary tumor tissues (24,25). It also has been shown that highly metastatic and estrogen-independent tumors secrete high levels of PGE 2 (24,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 expression is induced by cytokines and growth factors at sites of inflammation and is usually not detected in normal tissues [94]. Increased COX-2 expression and PGE 2 production has been reported in human colon carcinoma [95], breast cancer [96,97], renal cell carcinoma [98], and lung carcinoma [99].…”
Section: Pgementioning
confidence: 99%